Respuestas afectivas del adolescente a la agresión paterna - Jara Carreño, Ginna Briggite (2015)
The objective of the research is to identify the affective manifestations of the teenager attacked fatherly way, relying on the theories applied to the research support as fundamental to verify that the affective part of the father toward his son is not expressed in a positive way. In this way was related the affective manifestations of the teenager attacked paternally with the cognitive behavioral approach is geared to give changes in the behavior of the people, by reducing the behaviors, thoughts, or ideas that have the irrational teenager before the events immersed in their life and at the same time know what would be the support of the adolescent affective if it is not to become a future aggressor, creating goals in the patient so that this area is exceeded. The sample consisted of a 15-year-old boy, which complies with the clinical area to a study by applying qualitative interviews and reagents of incomplete sentences created by Joseph M. sacks in 1948 to obtain clinical material in the context of the family and the drawing of the family created by Porot (1952) is founded on the technique in the free drawing coming to know the feelings he has toward their families mainly from its parent and reflecting the situation in which is placed the adolescent with their environment. The discussion of the results are based on the psychological techniques applied, concluding that the adolescente assaulted does not have a favorable emotional bond within the family unit, resulting in an imbalance in the emotional part sentimental and developing a state of vulnerability in their personalidad.